Effect of Fiber Orientation Angle on the Failure Mode of Pin Jointed Laminated Composite Plates - Turan, Kadir; Kaman, Mete Onur; Gur, Mustafa (Pamukkale Univ, 2010)
In this study, the major aim is to investigate change effects of fiber orientation angles on the failure loads and failure modes for the pin jointed laminated composite plates. In the analysis, laminated composite plates with epoxy matrix resin reinforced unidirectional carbon fibers are used. The ply arrangements are chosen [theta degrees](4) and theta; fiber reinforced angle changes from 0 degrees to 90 degrees with 15 degrees increments. The failure load and failure mode are analyzed experimentally and numerically. In the numerical analysis Ansys program is used. In the program, material properties are degraded using APDL code which is written for progressive failure analysis and contains Hashin failure criteria for laminated composite plates. In the experimental study, the maximum failure load for [15 degrees](4) laminae cofiguration, 749.917 N and minimum failure load for [60 degrees](4), 467.483 N laminae configuration are obtained. A good agreement between experimental and numerical solution is obtained.
Keywords: Laminated composite materials; Progressive failure analysis; Pin joints; Finite element method